Modification of The Thermal Comfort Index Based on Perceptions for Urban Tourism Around Jakarta - Hidayat, Nizar Manarul; Hidayati, Rini; Turyanti, Ana; Al Maula, Sugha Faiz (Jurnal Meteorologi dan Geofisika, 2024)
Climate interaction directly correlates with an individual's comfort response. One's comfort can be quantified by perceiving environmental conditions at tourist locations. This study aims to identify climatic and non-climatic factors that affect thermal comfort based on visitor perception. In addition, the Holiday Climate Index (HCI) is modified to equalize visitors' perceptions. The research locations, namely Taman Mini Indonesia Indah (TMII), Kebun Raya Bogor (KRB), and Taman Safari Indonesia (TSI), are characterized by distinct topographies. This study identifies thermal comfort factors based on 552 questionnaire responses from purposive sampling. Analyzing factors influencing thermal comfort using ordinal logistic regression with Uncomfortable Class (0) and Comfortable Class (1). Model performance metrics, such as accuracy, precision, recall, and F1 score, are calculated using a confusion matrix. In general, the best time to feel comfortable is in the morning. Overall, climatic factors such as thermal sensation and rainfall events influence thermal comfort, while non-climatic factors have no effect. The model's implication is to provide an equation in the probability of someone feeling comfortable or uncomfortable based on the predictors. Furthermore, a modification index at TMII adjusted the HCI-urban's weighting, ratings, and comfort thresholds to match visitors' perceptions at that time. The results demonstrate that HCI-urban effectively provides comfortable and comfortable assessments. However, it has not yet been able to capture perceptions of discomfort, unlike the modified index. This research can provide added value to the tourism industry in terms of maintaining environmental comfort during the dry season.